Electrochemical preparation of luminescent graphene quantum dots from multiwalled carbon nanotubes - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemistry-A European Journal, 2012)
Green luminescent, graphene quantum dots (GQDs) with a uniform size of 3, 5, and 8.2(+/- 0.3) nm in diameter were prepared electrochemically from MWCNTs in propylene carbonate by using LiClO4 at 90?degrees C, whereas similar particles of 23(+/- 2) nm were obtained at 30?degrees C under identical conditions. Both these sets of GQDs displayed a remarkable quantum efficiency of 6.3 and 5.1?%, respectively. This method offers a novel strategy to synthesise size-tunable GQDs as evidenced by multiple characterisation techniques like transmission and scanning electron microscopy, atomic force microscopy, Raman spectroscopy and X-ray diffraction (XRD). Photoluminescence of these GQDs can be tailored by size variation through a systematic change in key process parameters, like diameter of carbon nanotube, electric field, concentration of supporting electrolyte and temperature. GQDs are promising candidates for a variety of applications, such as biomarkers, nanoelectronic devices and chemosensors due to their unique features, like high photostability, biocompatibility, nontoxicity and tunable solubility in water.
Keywords: electrochemical synthesis; graphene; Nanostructures; photoluminescence; quantum dots